Gratitude Can Increase Resilience in Adolescents Who Live in Orphanages - Bernadetha Putri Puspita; Yulia Ayriza (Journal Research of Social Science, Economics, and Management, 2022)
Resilience is the ability to endure and face and resolve problems or pressures. This is what adolescents who live in orphanages must have. Adolescents who live in orphanages are included in the children at risk group, where these adolescents tend to have a greater chance of experiencing shocks in terms of emotions, intellectuals, social and behavior. In increasing resilience, one of them is by having gratitude. This literature review aims to show that the important role of gratitude can increase resilience in adolescents who live in orphanages. There are several situations that can make the orphanage youth depressed, for example the lack of attachment between the foster child and the caregiver, the regulations in the orphanage that are not in accordance with the condition of the adolescents, limited facilities and other situations. This is what makes adolescents in orphanages need to have good resilience in order to have the ability to survive and face and solve problems or pressures. This paper is expected to help increase the role of gratitude so that adolescents who live in orphanages have good resilience.